Nilai-Nilai Pendidikan Islam Dalam Film Battle Of Empires Fetih 1453 - Ath-Thukhi, Ahmad Muhammad; Marianti, Erika; Adel, Samiullah; Burhanuddin, Burhanuddin; Arifin, Zainul (Khalifa Journal of Islamic Education, 2022)
Muhammad Al-Fatih (1432-1481) is one of prominent Islamic figures who is famous for his phenomenal bravery in conquering Constantinople in 1453 AD. The history of the conquest could be read in various Islamic history books. The epic story is even filmed through the movie of Battle of Empires Fetih 1453. The movie undoubtedly brings positive vibes for its Islamic educational values. Thus, this article is aimed at exploring of any possible Islamic educational values attached in the movie. The exploration is conducted through qualitative method of content analysis approach. The data was collected was one of movie scene of Battle of Empires Fetih 1453. All data were then analyzed using the Miles and Huberman technique with the stages of collecting, reducing and analyzing data and drawing conclusions. It is finally found that there are fourten Islamic educational values in the movie; six Islamic educational values related to Aqidah, three values related to worshipping (Ibadah) aspects and five values related to Akhlak. This findings is expected to give any ideas of new Islamic learning resources; movies. Besides, it is also ecouraged that the values in the movie could be another inspiration for the forthcoming Islamic generation as a young Islamic generation